PENGARUH MOTIVASI KERJA TERHADAP KINERJA PUSTAKAWAN LINGKUP KEMENTERIAN PERTANIANIAN - Erriani Kristiyaningsih (Ikatan Pustakawan Indonesia, 2019)
The achievement of librarian performance is closely related to the purpose of its agency. Librarians within the scope of the Ministry of Agriculture are librarians who are appointed through the selection of Civil Servant registration and regulated Performance by Minister of Administrative Reform Decree No. 132 / KEP / M.PAN / 12/2002 on Functional Position of Librarian and Credit Score. Achieving optimal performance requires a boost in running it. The motivation for work is a good driver factor not separated. This study aimed to analyzed how motivational factors significantly affect the performance of librarians scope of the Ministry of Agriculture. The study was conducted on 30 institutions under the Ministry of Agriculture with the number of respondents as much as 72 respondents. The result shows that motivating factors that affect the performance of librarians in the scope of the ministry of agriculture namely working conditions and salary/allowances. While the policy, quality of supervision, and interpersonal relationships do not affect the performance of librarians.